2022
DOI: 10.1021/acsnano.2c02812
|View full text |Cite
|
Sign up to set email alerts
|

Laser Processing of Flexible In-Plane Micro-supercapacitors: Progresses in Advanced Manufacturing of Nanostructured Electrodes

Abstract: Flexible in-plane architecture micro-supercapacitors (MSCs) are competitive candidates for on-chip miniature energy storage applications owing to their light weight, small size, high flexibility, as well as the advantages of short charging time, high power density, and long cycle life. However, tedious and time-consuming processes are required for the manufacturing of high-resolution interdigital electrodes using conventional approaches. In contrast, the laser processing technique enables high-efficiency high-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(41 citation statements)
references
References 265 publications
0
21
0
Order By: Relevance
“…Many studies have reported the fabrication of MO/graphene hybrid electrodes using hydrothermal methods having a simple procedure, microwave-assisted synthesis providing rapid synthesis, electrochemical deposition, laser processing, and chemical bath deposition (CBD) . The electrochemical deposition and laser processing can control the surface structure, size, and shape of the electrode elaborately by controlling the electrochemical conditions . CBD, with a simple process, has the advantage of being able to be performed at a low temperature .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have reported the fabrication of MO/graphene hybrid electrodes using hydrothermal methods having a simple procedure, microwave-assisted synthesis providing rapid synthesis, electrochemical deposition, laser processing, and chemical bath deposition (CBD) . The electrochemical deposition and laser processing can control the surface structure, size, and shape of the electrode elaborately by controlling the electrochemical conditions . CBD, with a simple process, has the advantage of being able to be performed at a low temperature .…”
Section: Introductionmentioning
confidence: 99%
“… 19 The electrochemical deposition and laser processing can control the surface structure, size, and shape of the electrode elaborately by controlling the electrochemical conditions. 20 CBD, with a simple process, has the advantage of being able to be performed at a low temperature. 21 These synthesis methods are variously used in the synthesis of hybrid electrodes according to the manufacturing requirements.…”
Section: Introductionmentioning
confidence: 99%
“…The laser scribing strategy has emerged as a scalable and time-saving technique to engrave high-resolution patterns with precisely controlled laser parameters, including laser power, processing speed, processing time, resolution, frequency and Z axis offset. 73 Various laser wavelengths ranging from ultraviolet (UV) to infrared (IR) regions have been developed to scribe film structure materials into patterned electrodes. 74,75 According to the requirements of processing efficiency and precision, the laser wavelength should be rigorously controlled by computer systems.…”
Section: Laser Scribingmentioning
confidence: 99%
“…4 Additionally, there is no development and rinsing in ultrafast laser processing; therefore, it has the advantages of few steps, no mask, fast processing and environmental friendliness. [5][6][7] These merits lead to many applications in a variety of aspects, such as the use of ultrafast laser-induced microexplosion to create and recover high-density polymorphs, 8 ultrafast laser pulse for building photonic lattices, 9 and direct nanowriting in air. 10 Also, these characteristics enable ultrafast laser to achieve ultrahigh precision in the processing of three-dimensional (3D) micro/nano structures.…”
Section: Introductionmentioning
confidence: 99%